The Reconfiguration of Kaduna Municipal Area Distribution Network for Power Loss Reduction and Voltage Profile Improvement Using Static Var Compensators (SVC) - Abel Ehinem Airoboman; Bukar Alhaji Bukar; I.A Araga (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
The increase in global and Nigerian demand for electricity due to technological advancements has brought about numerous challenges, including voltage instability, power factor problems, and high-power losses in electrical power distribution networks. This paper presents the placement of a Static Var Compensator (SVC) in the power distribution network of Town One Station, Kaduna, Nigeria, to investigate its impact on improving and addressing the network’s poor voltage profile and reducing the active powerloss experienced by the network. For analysis, the bus voltage, power, and the current passing through the chosen feeders were measured and noted appropriately. The network parameters, including route length, transformer parameters, and maximum power flow, were obtained from the Kaduna Electricity Distribution Company in Kaduna, Nigeria. The distribution network was modelled and simulated in the ETAP software environment, both with and without Static Var Compensator (SVCs). The results obtained fromthe simulation indicated that buses 5, 7, 8, and 47, among others, have a voltage magnitude of 0.743– 0.932 pu, which is clearly outside the acceptable limit of 0.95– 1.05 pu. Further results showed that the network experienced real and reactive power losses of 8,527 kW and 23,535 kVAr, respectively. After the placement of the SVC with a 5.75MVAR rating, the active power loss decreased from 8527 kW to 6751 kW, indicating a 20.82% reduction in total active power loss experienced by the network. Additionally, the minimum network’s bus voltage improved from 0.743 to 1.02 p.u.